Numerical investigation of in-cylinder gas motion dynamics in a heavy-duty direct injection hydrogen internal combustion engine - Akar, Firat; Ozener, Orkun (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Mixture homogenization is one of the most important parameter for hydrogen internal combustion engines (H2ICE) to achieve near-zero NOx emissions and stable combustion, especially when premixed combustion strategy is used. On the other hand, inhomogeneities are inevitable due to the limited duration for mixing. This is more prominent in H2ICEs; those adopts low pressure direct injection (LPDI) system. Optimizing an engine to achieve higher level of homogeneity requires profound understanding of in-cylinder gas motion and mixing dynamics. To establish deeper comprehension of gas motion inside the cylinder, a 13-L LPDI H2ICE was modelled, and effect of different parameters were investigated by a holistic 1D-3D simulation methodology. While boundary conditions of operating point were obtained from the 1D simulations, different swirl numbers (SN), piston shapes and injector cap designs were simulated with 3D-CFD. Simulation results were analyzed based on uniquely defined parameters like homogeneity index (HI) and symmetricity of motion (SOM), as well as standard parameters like turbulence kinetic energy (TKE), and 3D visualizations of equivalence ratio iso-surfaces. Analysis showed that, there is a negative correlation between SN and HI under investigated conditions. Moreover, it was found that piston shapes which are promoting the tumble motion, improved average TKE by 31% and HI by 28% over base piston. This study aims to be a reference for the in-cylinder gas motion design of ultra-lean LPDI H2ICEs, where the target is retrofitting an existing diesel engine and attaining the best HI, SOM and TKE values at rated power conditions.
Keywords: Hydrogen engine; Mixture homogenization; Lens piston; Tumble; Ultra-lean; Injector cap; IGNITION ENGINE; EMISSIONS; Chemistry; Electrochemistry; Energy & Fuels